Controls of point and diffuse sources lowered riverine nutrient concentrations asynchronously, thereby warping molar N:P ratios. (18th September 2020) - Westphal, Katja; Musolff, Andreas; Graeber, Daniel; Borchardt, Dietrich
Abstract: The input of nitrogen (N) and phosphorus (P) into rivers has been reduced in recent decades in many regions of the world to mitigate adverse eutrophication effects. However, legislation focused first on the reduction of nutrient loads from point sources and only later on diffuse sources. These reduction strategies have implications on riverine N:P stoichiometry, which potentially alter patterns of algal nutrient limitation and the functions or community structure of aquatic ecosystems. Here, we use a dataset spanning four decades of water quality for the Ruhr River (Germany) to show that the asynchronous implementation of point and diffuse source mitigation measures combined with time lags of catchment transport processes caused a temporally asynchronous reduction in dissolved inorganic nitrogen and total phosphorus concentrations. This asynchronous reduction increased the molar N:P ratios from around 30 to 100 in the river sections dominated by point sources, reducing the probability of N limitation of algae in favor of P limitation. The Ruhr River catchment and the environmental policies implemented here illustrate the unintended effects of nutrient control strategies on the ecological stoichiometry at the catchment scale. We urge to assess systematically, whether unintentionally warped macronutrient ratios are observable in other managed river systems and to evaluate their environmental impacts.